Air pollution, pollutant emissions and harmfull effects - Aydın, Hüseyin; İlkılıç, Cumali (Batman Üniversitesi, 2017)
Present paper is an overview of the engine and air pollution problem especially in the urban areas. Air pollution is caused bu pollutant emissions is popular problem that should be solved in the world by means of its harmfull effects. The combustion processes of diesel and gasoline fuels in realted engines and other hydrocarbon fuels in termical machines are main sources of air pollutant emissions. These main pollutants are nitrogen oxides (NOx), carbon dioxide (CO2), sulphur oxides (SOx), hydrocarbons (HC), carbon monoxide (CO), particulates matter (PM), lead (Pb), and volatile organic compounds (VOCs). All these emissions are firstly introduced and classified in the view of their sorces and formation processes. Then, their negative and harmfull effects on global warming, environment and human healt have been presented. Finaly the processes and technologies of reducing these pollutant emissions were presented.

Present paper is an overview of the engine and air pollution problem especially in the urban areas. Air pollution is caused bu pollutant emissions is popular problem that should be solved in the world by means of its harmfull effects. The combustion processes of diesel and gasoline fuels in realted engines and other hydrocarbon fuels in termical machines are main sources of air pollutant emissions. These main pollutants are nitrogen oxides (NOx), carbon dioxide (CO2), sulphur oxides (SOx), hydrocarbons (HC), carbon monoxide (CO), particulates matter (PM), lead (Pb), and volatile organic compounds (VOCs). All these emissions are firstly introduced and classified in the view of their sorces and formation processes. Then, their negative and harmfull effects on global warming, environment and human healt have been presented. Finaly the processes and technologies of reducing these pollutant emissions were presented.
Air pollution, pollutant emissions and harmfull effects